Proper Distal Placement of Tibial Nail Improves Rate of Malalignment for Distal Tibia Fractures. Issue 12 (December 2017) - Triantafillou, Konstantinos; Barcak, Eric; Villarreal, Arturo; Collinge, Cory; Perez, Edward
Abstract : Objectives: We hypothesize that the anatomic center of the distal tibia is just lateral and anterior to the center of the distal tibia articular surface in the coronal and sagittal planes, respectively, and that placement of the nail along this axis results in improved rates of malalignment when treating distal tibia fractures. Design: Retrospective study. Level of Evidence: Therapeutic Level IV. See Instructions for Authors for a complete description of levels of evidence. Setting: One Level I and one Level II trauma center. Patients/Participants: Two hundred three distal tibia fractures treated with intramedullary nailing (IMN) (primary cohort) whose main fracture line extended within 5 cm of the plafond to evaluate the rate of malalignment with distal nail placement. Additionally, we retrospectively reviewed a secondary cohort of 15 patients with proximal tibia fractures treated with intramedullary nailing for evaluation of passive anatomic distal nail position. Main Outcome Measures: Primary malalignment ⩽5 degrees on the anteroposterior (AP), mortise, and lateral planes were evaluated in distal tibia fractures on perioperative radiographs. Results: Primary Cohort: 85 patients met inclusion criteria for evaluation in the coronal plane. Overall malalignment in the coronal plane was 17.6%. There was a 2.9% (1/34) fracture malalignment rate when the nail was placed lateral to the center of the joint versus 27.5% (14/51) when placed medial to the center of the joint, with all occurring in valgus. This achieved statistical significance ( P = 0.04). Correlation was highest when measuring the trajectory on mortise view using the talus as reference point. When evaluating the sagittal plane, there were 64 patients that met inclusion criteria with a 48% malalignment rate. Malalignment was greatest when the nail was placed in the anterior quadrant 100% (4/4), versus 50% (22/44) in the anterior middle, and 31.3% (5/16) in the posterior middle quadrant. This achieved statistical significance ( P = 0.05). No nails were placed in the most posterior quadrant. Secondary Cohort: 15 patients met inclusion criteria for distal nail placement. The position of the nail in the coronal plane was measured on both the anteroposterior and mortise ankle radiographs using both the plafond and talus as a reference, whereas sagittal nail placement was measured on the lateral ankle radiographs. In the coronal plane, the mean passive distal position of the nail when referenced from the lateral cortex was 45.2% of the tibia plafond and 45.5% the width of the talus, or just lateral to the center of each. In the sagittal plane, passive nail placement was 40% the sagittal width of the joint measured from the anterior cortex, or just anterior to the center of the joint. Conclusions: This is the first patient series that defines optimal tibial nail placement in the treatment of distal tibia fractures. Distal placement of the nail just lateral to the center of the talus and plafond, or along mechanical axis of the tibia, results in significantly reduced rates of malalignment on the coronal plane when compared to nail placement medial to the center of the talus or plafond. Fluoroscopic judgment of distal nail trajectory was improved on the mortise view using the talus as a reference when compared to using the anteroposterior view. On the sagittal plane, anatomic passive nail placement is just anterior to the center of the plafond. However, nonanatomic nail placement just posterior to the center of the plafond had a lower incidence of malalignment compared with nails placed anterior to the center of the plafond. Further study of appropriate nail positioning on the sagittal plane is needed.